Efektivitas Penerapan Tax Amnesty di Indonesia - Nur Asyiah Jamil (Academica: Journal of Multidisciplinary Studies, 2017)
This article wrote to describe the level of effectiveness of the tax, especially tax revenues and tax obedience in Indonesia. With descriptive approach method by analyzing the source which relating to the implementation of tax amnesty, the result showed that the application of the tax amnesty has not been effective. The Government should find the right solution to improve the effectiveness of the tax in Indonesia. The improved system of taxation and appropriate policy will increase the effectiveness of tax implementation in Indonesia.Keywords:Tax, Tax amnesty, Tax-policy